Phosphite Reduces the Predation Impact of Poterioochromonas malhamensis on Cyanobacterial Culture - Narumi Toda; Hiroki Murakami; Akihiro Kanbara; Akio Kuroda; Ryuichi Hirota (Plants, 2021)
Contamination by the predatory zooplankton Poterioochromonas malhamensis is one of the major threats that causes catastrophic damage to commercial-scale microalgal cultivation. However, knowledge of how to manage predator contamination is limited. Previously, we established a phosphite (Pt)-based culture system by engineering Synechococcus elongatus, which exerted a competitive growth advantage against microbial contaminants that compete with phosphate source. Here, we examined whether Pt is effective in suppressing predator-type contamination. Co-culture experiment of Synechococcus with isolated P. malhamensis revealed that, although an addition of Pt at low concentrations up to 2.0 mM was not effective, increased dosage of Pt (~20 mM) resulted in the reduced grazing impact of P. malhamensis. By using unsterilized raw environmental water collected from rivers or ponds, we found that the suppression effect of Pt was dependent on the type of environmental water used. Eukaryotic microbial community analysis of the cultures using environmental water samples revealed that Paraphysomonas, a colorless Chrysophyceae, emerged and dominated under high-Pt conditions, suggesting that Paraphysomonas is insensitive to Pt compared to P. malhamensis. These findings may provide a clue for developing a strategy to reduce the impact of grazer contamination in commercial-scale microalgal cultivation.